A Circadian Clock in the Retina Regulates Rod-Cone Gap Junction Coupling and Neuronal Light Responses via Activation of Adenosine A2A Receptors - Cao, Jiexin; Ribelayga, Christophe P.; Mangel, Stuart C. (Frontiers in Cellular Neuroscience, 2021)
Adenosine, a major neuromodulator in the central nervous system, is involved in a variety of regulatory functions such as the sleep/wake cycle. Because exogenous adenosine displays dark- and night-mimicking effects in the vertebrate retina, we tested the hypothesis that a circadian (24-hr) clock in the retina uses adenosine to control neuronal light responses and information processing. Using a variety of techniques in the intact goldfish retina including measurements of adenosine overflow and content, tracer labeling, and electrical recording of the light responses of cone photoreceptor cells and cone horizontal cells, which are post-synaptic to cones, we demonstrate that a circadian clock in the retina itself – but not activation of melatonin or dopamine receptors - controls extracellular and intracellular adenosine levels so that they are highest during the subjective night. Moreover, the results show that the clock increases extracellular adenosine at night by enhancing adenosine content so that inward adenosine transport ceases. In addition, we report that circadian clock control of endogenous cone adenosine A2A receptor activation increases rod-cone gap junction coupling and rod input to cones and cone horizontal cells at night. These results demonstrate that adenosine and A2A receptor activity are controlled by a circadian clock in the retina, and are used by the clock to modulate rod-cone electrical synapses and the sensitivity of cones and cone horizontal cells to very dim light stimuli. Moreover, the adenosine system represents a separate circadian-controlled pathway in the retina that is independent of the melatonin/dopamine pathway but which nevertheless acts in concert to enhance the day/night difference in rod-cone coupling.